Transient Hemi-Lower Limb Ischemia in the Newborn: Arterial Thrombosis or Persistent Sciatic Artery? - Makiko Kirino; Masayuki Ochiai; Masako Ichiyama; Hirosuke Inoue; Takeshi Kusuda; Tadamune Kinjo; Masataka Ishimura; Shouichi Ohga (Thieme Medical Publishers, Inc., 2017)
Abstract Neonatal thromboembolism occurs with various predispositions and triggers. Early diagnosis of the thrombosis is challenging and essential for the therapeutic interventions. We herein report two newborns who presented with transient hemi-lower limb ischemia due to (1) arterial thrombosis or (2) a persistent sciatic artery (PSA). The patient with arterial thrombosis showed elevations of fibrin degradation product and D-dimer and received antithrombin and heparin intravenously. The patient with PSA was immediately assessed by a contrast-enhanced computed tomography because of a transient ischemic episode with no evidence of hypercoagulability. Newborns suspected of having arterial thrombosis may need urgent surgical intervention along with thrombolytic and anticoagulant therapy to prevent organ ischemia and amputation of extremities. Conversely, some PSA cases have reportedly been treated conservatively. This vascular anomaly was previously reported as a cause of lower limb ischemia only in a newborn. PSA is a critical differential diagnosis of neonatal arterial thrombosis that needs urgent therapeutic intervention.